An overview of the market for credit risk transfer - Boyer, Martin; Papageorgiou, Nicolas (Assurances et gestion des risques / Insurance and Risk Management, 2005)
In a previous article in Assurances et gestion des risques, Boyer and Papageorgiou (2004) discussed the implications of the new Basel accord to credit risk management. In the column, we will look at the financial markets and instruments that have been developed in order to satisfy the ever growing demand for credit risk management tools. We will describe the main credit derivatives and structured products that have become increasingly important in financial markets, and provide some insights into the latest trends in credit risk.